Motivation, Attitudes and Learning Strategies: Motivated Learning In University Students - Boza Carreño, Ángel; Tosca, María de la O (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
This work evaluates the factors associated with motivated learning of university students. Using a Linker scale, we evaluate the goals, attitudes, motives for learning. We also evaluate the conditions, strategies and involvement in the study. The objective is to identify the differences between the most motivated students and less motivated students. The sample, stratified random proportional, is of 938 students at the University of Huelva. The results are the following distinguishing characteristics of university students’ motivated learning: a cognitive, social and task goals, a learning attitude oriented to success, a self attribution of success, and some reasons for studying work-related future. These students are also competent in the study, combining ability of individual and team work, use more learning strategies, and engage in the study.